On the dispersion of Lamb waves in an elastic layer interacting with the ideal liquid half-space - Bahno, O.M. (Reports of the National Academy of Sciences of Ukraine, 2017)
The propagation of quasi-Lamb waves in the system «ideal compressible liquid half-space — elastic layer» is studied, by using the three-dimensional equations of classical elasticity theory for a solid body and linearized Euler equations for a fluid. The dispersion curves for normal waves over a wide range of frequencies are constructed. The influence of an ideal compressible fluid and the thickness of an elastic layer on the dispersion of phase velocities of the quasi-Lamb modes in a hydroelastic waveguide is analyzed. The localization properties of the lower quasi-Lamb modes in hydroelastic waveguides are studied. A criterion for the existence of the quasi-Lamb waves in hydroelastic waveguides is proposed. The numerical results obtained are presented in the form of plots and analyzed.